ANALISIS KONSEPTUAL TEORETIK PENDIDIKAN KEWIRAUSAHAAN SEBAGAI SOLUSI DAMPAK ERA INDUSTRI 4.0 DI INDONESIA - Sumarno Sumarno; Gimin Gimin (JURNAL PENDIDIKAN EKONOMI: Jurnal Ilmiah Ilmu Pendidikan, Ilmu Ekonomi dan Ilmu Sosial, 2019)
This article aims to find out entrepreneurial education as a solution to the impact of the industrial era 4.0 (E.I.4.0). The data were collected by documentation techniques and observation, and then analyzed using descriptive exploratory techniques. The results indicate that E.I.4.0 had a negative impact is the loss of various jobs, but on the other hand had a positive impact, that are the emergence of business and employment opportunities. In E.I.4.0, human resources are required to have the ability to create, innovate, think critically, and collaborate and self-confidence. Entrepreneurship education provides knowledge and skills and develops attitudes that can be a solution to the impact of E.I 4.0. Entrepreneurial knowledge, skills and attitudes will shape human beings in accordance with E.I.4.0, which were the ability to create, innovate, think critically, collaborate, and be confident. This ability will be able to reach opportunities that arise in order to replace lost jobs. At the level of pre-school education, basic education and general secondary education (SMA/MA), entrepreneurship education should be emphasized more on developing entrepreneurial attitudes and knowledge. At the level of vocational secondary education (SMK/MAK) and higher education, entrepreneurship education should be emphasized more on the development of entrepreneurial skills. Effective implementation of entrepreneurship education for E.I.4.0 requires synergy and integration between subjects or subjects, teachers / lecturers, education levels, and among various stakeholders in a sustainable. Keywords: Industrial era 4.0, entrepreneurship, entrepreneurship education.